Growth Optimization of Multi-layer Thin Film Thermoelectric Materials based on Bi2Te3 / WS2 superlattice Structure. (2019) - Mbaye, Mamadou T.; Howe, Andrew; Pradhan, Sangram K.; Xiao, Bo; Bahoura, Messaoud
Abstract: Heat is the most ubiquitous form of energy on planet Earth. Every day, the sun continuously strikes the Earth's surface with 120, 000 Terawatts of energy. This solar energy is more than 10, 000 times the amount of energy produced worldwide. With the scarcity of fossil fuels looming on the horizon and its adverse effect on the environment many researchers, from academia to industry, are exploring cleaner, greener and more efficient renewable energy technologies. Thermoelectricity can provide an alternative to hazardous fossil fuels as its electricity is produced directly from heat with no moving parts or working fluid. The efficiency of any thermoelectric material is given by a quantity called the figure of merit ZT. For thermoelectric (TE) devices to be competitive with fluid-based and other energy related devices, ZT greater than 2 is usually sought. Here, we report on the fabrication of thin film thermoelectric materials based on Bi2 Te3 /WS2 superlattice layer structure using RF magnetron sputtering deposition method. Quantum confinement in these low dimensional and ultrathin superlattices can enhance the density of states near the fermi level resulting in higher ZT value. The thermoelectric figure of merit can be enhanced by controlling the layer thickness close to the phonons mean free path. This way heat carrying phonons with different wavelengths can be scattered efficiently resulting in lower lattice thermal conductivity.